The European financial crisis : debt, growth, and economic policy - Godby, Robert (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2014)
The European debt crisis has posed a challenge for many people to understand, both non-Europeans and Europeans alike. Even economists, finance specialists, and market commentators are often uncertain of its causes or in the interpretation of events ongoing, or of past events that have taken place that then shaped the current situation. Typically, this lack of comprehension results from a lack of understanding of how European institutions work, the structure of European politics and the Eurozone, the economics of the financial system, or the relationship of debt markets to current government policies in the European Union (EU). The purpose of this book is to describe the causes and outcomes of the European debt crisis (to the date of publication) within the context of three questions most often asked about the debt crisis: (i) what happened, (ii) why did it happen, and (iii) why has the crisis been so difficult for policy makers to address?
Acknowledgements -- Part I. Introduction: understanding the problem. Why is this so hard? -- 1. Introduction: where there's smoke, there's fire -- Part II. The imperfect architecture of the Eurozone -- 2. The flawed governmental architecture of the Eurozone -- 3. The flawed economic architecture of the Eurozone -- 4. The flawed sociopolitical architecture of the Eurozone -- Part III. Evolution of the Euro crisis -- 5. Flight of the bumblebee: precrisis structural imbalances and their influence in the Eurozone -- 6. Misperception of European risk, market reactions, and policy response: a timeline of the Euro crisis -- Part IV. Moving forward -- 7. Where are we now? -- 8. What happens next? -- 9. From forest fires to bumblebees and hammers and nails, lessons from the Euro crisis -- Notes -- References -- About the author -- Index.
Part of: 2014 digital library.
Includes bibliographical references (pages 213-216) and index.
Title from PDF title page (viewed on January 4, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Financial crises -- Europe; Europe -- Economic conditions -- 21st century; European debt crisis; European politics; European Union; EU; European integration; sovereign debt; currency union; monetary policy; fiscal policy; EU institutions; debt crisis timeline; the Euro; Greek debt crisis; macroeconomics; recession; banking union; Eurozone; bailouts; currency risk; bond risk; financial uncertainty; central bank policy; central bank independence; Germany; ECB; European Central Bank; IMF; International Monetary Fund; the troika; European unemployment; Electronic books